The strong freshwater anomaly during the onset of the 2015/2016 El Niño - F. Gasparin; D. Roemmich (Geophysical Research Letters)
Abstract The strong freshwater anomaly in the equatorial Pacific is investigated during the onset of the 2015/2016 El Niño using oceanic observational data sets and atmospheric reanalyzes. The 2015 salinity patterns are marked by a large equatorial freshwater anomaly whose extensive spatial and large amplitude characteristics have not previously been captured in the 2004–2014 Argo record. As the main contributors of the freshwater budget, zonal advection and surface forcing have similar amplitude but with maxima located at different longitudes around the dateline. The comparison of the substantial rainfall and westerly winds observed in 2015 with the 2009 and 1997 El Niño onset years shows that 2015 characteristics combine both typical salinity‐related patterns of Central and Eastern Pacific El Niños. Dynamically, this large freshwater anomaly causes a positive steric height anomaly in the western Pacific and increases eastward surface acceleration at the SSS front due to the zonal pressure gradient.